A quick course in the History of History and the History of Law (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This paper will seek to present the evolution of law alongside the evolution of man and the most prominent societies in which he has lived, from prehistoric times to the most recent events of the contemporary era. Many of the legal devices that today seem commonplace in forensic and academic practice have their origins unknown to the vast majority of legal professionals. The application of a legal institute in a petition, an appeal, an oratory, a sentence, knowing its origin and purpose, makes the action of the professional, the academic or the simple citizen much more effective when it comes to claiming their rights.
Keywords: History of Law; Evolution of Law; Principles of Law; Roman Law; Canon Law; Common Law; Civil Law